The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/jnci/djy218
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Heart Failure and Other Cardiovascular Hospitalizations After Early Stage Breast Cancer: A Matched Cohort Study

Abstract: Background Data are limited regarding the risk of heart failure (HF) requiring hospital-based care after early stage breast cancer (EBC) and its relationship to other types of cardiovascular disease (CVD). Methods We conducted a population-based, retrospective cohort study of EBC patients (diagnosed April 1, 2005–March 31, 2015) matched 1:3 on birth-year to cancer-free control subjects. We identified hospitalizations and emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 52 publications
(34 reference statements)
4
55
4
Order By: Relevance
“…Contrary to our results, Abel-Qadir et al [11] found that the prevalence of different types of CVD was signi cantly higher in BC patients compared to cancerfree controls. A possible explanation for this discrepancy could be that Abel-Qadir et al used different algorithms to determine the presence of CVD preceding the index date.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results, Abel-Qadir et al [11] found that the prevalence of different types of CVD was signi cantly higher in BC patients compared to cancerfree controls. A possible explanation for this discrepancy could be that Abel-Qadir et al used different algorithms to determine the presence of CVD preceding the index date.…”
Section: Discussioncontrasting
confidence: 99%
“…Abel-Qadir et al [11] found a signi cantly higher incidence of CVD hospitalizations due to heart failure, cerebrovascular disease and arrhythmias in BC patients compared to cancer-free controls whereas we did not nd this for cerebrovascular disease or arrhythmias. In accordance with our results, Strongman et al [12] found a statistically signi cantly higher incidence of heart failure and venous thromboembolism in BC patients compared to cancer-free controls, but not signi cant differences in the incidence of arrhythmia, stroke or peripheral vascular disease.…”
Section: Discussioncontrasting
confidence: 97%
“…For example, the prevalence of cachexia is high (~50%) and greater in lung or colorectal cancers compared to breast cancer ( 3 ). Therefore, resistance training may be of particular interest for lung or colorectal cancer patients, while breast cancer patients may get more health benefits from aerobic exercise to focus on cardiovascular outcomes ( 9 , 50 ). However, it should be emphasized that this speculation is done without a global and comparative approach, which is needed for such a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…This variability appears to be accountable for the lack of tailored exercise interventions ( 49 ) and occurs due to the large number of parameters that influence the effects of exercise prescribed to patients: the type and stage of cancer, the type of treatment, and the physical status at the time of diagnosis. For example, lung cancer patients present a higher risk of cachexia, whereas breast cancer patients present a higher risk of heart failure ( 9 , 50 ). All these different parameters, and their evolution throughout treatment, should be considered in prescribing the best exercise strategies on an individual basis, as opposed to generic exercise programs.…”
Section: Introductionmentioning
confidence: 99%
“…In few cases, antimetabolite drugs, such as 5-fluorouracil, are related to myocardial infarction, heart failure, and arrhythmias 21 . A matched cohort study from Canada examining the risk of cardiovascular hospitalisation and heart failure demonstrated that the10-year incidence of cardiovascular disease hospitalisation was 10.8% for patients with breast cancer; moreover, 37% of their study population received anthracyclines and/or trastuzumab and the relative rate of cardiovascular disease was higher compared to their age-matched subjects 22 . In our study, we excluded those who received trastuzumab to simplify the division of the patients into four adjuvant groups that represented the majority of the breast cancer population.…”
Section: Discussionmentioning
confidence: 99%